Effect of stenosed and occluded coronary arteries on immediate and late myocardial uptake of thallium-201. Issue 2 (August 1981) - Clitsakis, D; Layton, C A; Battersby, W; Johns, M; Stockley, A V
Abstract : Exercise and redistribution myocardial scintigraphy using thallium-201 was compared with the left ventricular angiogram and with the presence of stenosis or occlusion of coronary arteries on angiography. Irreversible scintigraphic defects representing areas of myocardial infarction were found in all patients with occlusion of the left anterior descending artery but nearly one-third of patients with stenosis of that artery also showed evidence of infarction. For the right coronary or circumflex arteries the incidence of infarction was 82% with vessel occlusion and 57% with vessel stenosis. Of abnormally contracting segments on the left ventricular angiogram, 95% showed irreversible scintigraphic defects but 33% of normally contracting segments supplied by a diseased artery also showed this. Myocardial infarction is not uncommon in patients with angina even in the absence of coronary occlusion. The incidence is underestimated by the left ventricular angiogram. These findings are of importance in the assessment of patients with coronary disease and their evaluation before coronary artery surgery.